National traffic census / Siti Nornazira Md Hashim - Md Hashim, Siti Nornazira (2017)
Bangunan Pejabat Jabatan Kerja Raya Daerah Kota Tinggi originally in Bangunan Pejabat Penyelenggaraan Bangunan, Jalan, Elektrik dan Pelan located in Jalan Lombong dealing with Hospital Kota Tinggi and moved to Level 5, Bangunan Sultan Iskandar, Kota Tinggi, Johor and in 2009 moved to Jalan Abdul Aziz, Kota Tinggi The National Traffic Census is to be carried out with a view to assess the state of traffic flow on the road network and existing crossing in the proposed development area. Impact of development on the existing road network facility rated for a certain period will be identified. The study results allow recommendations road facility improvements made to overcome the problem of traffic expected. Furthermore, traffic census is to determine the national economy because they involving the use of vehicles that are used on a daily basis. There are 3 type of national traffic census which is Type ‘O’ that do in 5 March 2017 on 0600a.m. until 12 March 2017 0600a.m. Furthermore, Type ‘1’ that does in 5 March 2017 on 0600a.m. until 2200p.m. in the same day. Lastly, Type ‘3’ that do in the working day among 5 March 2017 to 12 March 2017 on 0600a.m. until 2200p.m. On station JKR Daerah Kota Tinggi that conducting traffic census Type ‘O’ that do in 5 March 2017 on 0600a.m. until 12 March 2017 0600a.m. But for the mobile station there choose Type ‘3’ start from 0600a.m. until 2200p.m. and it just on working day. The proposed site is divided into 9 area namely JR 401, JR 402, JR 403, JR 404, JR 405, JR 406, JR 407, JR 408 and JR 409. Classified volume count for the roadway turning movements were carried out manually in accordance to the Jabatan Kerja Raya (JKR) requirements to enumerate the actual volume of traffic along the selected roadway. Vehicle entering and leaving each survey station were recorded and classified into six (6) difference categories, namely cars and taxis, small vans and utilities, large vans and medium lorries, heavy lorries, buses, and motorcycles. This study found that this area is expected to generate high amount of vehicles especially during peak morning and afternoon hours.